2011
DOI: 10.1111/j.1745-4530.2009.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted Extraction and Liquid Chromatography/Mass Spectrometry Analysis of Flavonoids From Grapefruit Peel

Abstract: The flavonoids of grapefruit peel were obtained by microwave‐assisted extraction. Five constituents have been identified by liquid chromatography/mass spectrometry analysis such as hesperitin‐7‐O‐glucoside, isonaringin, naringin, 2′,5′‐dihydroxy‐3,4′,5,6,7‐pentamethoxyflavone and neoeriocitrin. The last two compounds are reported first in grapefruit peel. The effects of solvent, time, ratio of solvent to material (liquid/solid) and output power on the extraction were investigated. The results show that the bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…They include conventional solvent extraction, alkaline extraction (Bocco, Cuvelier, Richard, & Berset, 1998), microwave assisted extraction (Wang, Shang, Wang, & Feng, 2011), resin-based extraction (Di Mauro, Fallico, Passerini, & Maccarone, 2000), enzyme-assisted extraction (Li, Smith, & Hossain, 2006a), subcritical water extraction (Ko, Cheigh, & Chung, 2014) and supercritical fluid extraction (Giannuzzo, Boggetti, Nazareno, & Mishima, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They include conventional solvent extraction, alkaline extraction (Bocco, Cuvelier, Richard, & Berset, 1998), microwave assisted extraction (Wang, Shang, Wang, & Feng, 2011), resin-based extraction (Di Mauro, Fallico, Passerini, & Maccarone, 2000), enzyme-assisted extraction (Li, Smith, & Hossain, 2006a), subcritical water extraction (Ko, Cheigh, & Chung, 2014) and supercritical fluid extraction (Giannuzzo, Boggetti, Nazareno, & Mishima, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of these compounds is commonly performed through a conventional solvent extraction process (Xu et al 2007). In recent years, non-conventional extraction technologies like microwave, enzyme and ultrasound assisted extraction are also being the interest of scientific studies for maximizing yield (Garcia-Castello et al 2015;Li et al 2006;Wang et al 2011;Wilkins et al 2007). However, no comprehensive study is available on comparison of EAE with UAE and CSE for phytochemical recovery from peel of grapefruit grown under semiaridsubtropical Indian conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al optimised the extraction process using 80% ethanol as the extraction solvent, and they demonstrated that the optimal conditions were 3 min. of extraction time, 25 : 1 (ml g −1 ) as the liquid to solid ratio and 560 W of microwave power, 329 while Hayat et al focused on the use of methanol/water mixtures. 330 Under these conditions, a 5.81% extraction yield is obtained, which was higher than reflux and ultrasonic methods.…”
Section: Examples Of Food Waste Valorisationmentioning
confidence: 99%